Implementasi Kebijakan Kurikulum Merdeka di SD Negeri 043/VII Karang Mendapo II - Andri Ani Suryawijaya; Muhammad Aprizal; Hery Kiswanto; Riska Meisyi Putri; Anggia Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Independent Curriculum is a new policy of the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) designed to improve the quality of learning through flexibility, simplified materials, and a focus on developing student character and competencies. This study aims to describe the implementation of the Independent Curriculum at SD Negeri 043/VII Karang Mendapo II, including supporting and inhibiting factors, and the impact of its implementation on the learning process. The study used a qualitative case study approach, with data sources including the principal, teachers, students, and learning documents. Data were collected through observation, interviews, and document analysis. Data were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the Independent Curriculum has been implemented in stages and is supported by the readiness of school management and teachers' willingness to adapt. The impact is evident in increased student participation, more contextual learning, and teachers' role as facilitators. However, several obstacles were identified, such as varying teacher abilities in understanding teaching materials, limited collaboration within learning communities, and the suboptimal use of innovative learning media to support differentiated learning. The study recommends increased systematic training, ongoing mentoring, and optimized use of the Merdeka Mengajar digital platform.